MULTIWAVELENGTH VARIABILITY ANALYSIS OF BINARY SUPERMASSIVE BLACK HOLES BLAZAR OJ 287 USING DATA FROM UVOT AND XRT OF SWIFT MISSION (2005 ÃâÃâ 2017) - FATIMA (NIM: 20316008), SITI
OJ 287 is a bright blazar which has been studied intensively since 1980s and known has some optical outbursts. Characteristics of the optical outbursts such as the outburts period is ~12 years, there are double peaks in one period, and there is no color variability. From some proposed models, binary supermassive black holes (SMBH) blazar was confirmed as the best suitable model to explain the phenomena. In the model it is explained that minor SMBH has ellips orbit crossing the accretion disk of mayor SMBH. It is also explained that the mechanism of superflare (main double peaks) radiation source from bremsstrahlung process, while other peaks in outburts phase as non-thermal radiation. Therefore, beside optical investigation we also need to investigate OJ 287 in UV and X-ray to understand the behaviour in higher energies. In this research, we investigate the light curve and spectra of OJ 287 in multiwavelenght (optical, UV and X-ray) during 2005 Ã‚Â– 2017. The data was obtained from Swift/UVOT and Swift/XRT. We get confirmation that second superflare of 2001 Ã‚Â– 2010 decade was occured in October Ã‚Â– December 2007. While first superflare of 2011 Ã‚Â– 2020 decade was occured in October 2016 Ã‚Â– January 2017. X-ray spectra was analyzed in 0.3 Ã‚Â– 10 keV. In general, power law model was the best fit model for X-ray spectra of Oj 287 with photon index value, Γ, was variabel. Variability of Γ is suitable with inverse compton range (1 ≤ Γ ≤ 2,5) except for superflare 2016 Ã‚Â– 2017 spectrum, with value Γ ~ 2,6, which is more suitable with synchrothron model. In multiwavelength model, OJ 287 spectra in optic to X-ray range show that there is variablility with power law+ power law and bremsstrahlung+power law models indicate the combination of thermal and non-thermal radiation in optic Ã‚Â– UV. There is also indication of inverse compton component shifting to lower energy at the time of superflare 2016 Ã‚Â– 2017.